The Effect of Green Marketing and Corporate Social Responsibility on Brand Image of Emina Products - Faiza Dwi Rahmadhani; H Herliani; Adi Setiawan; Tiara Muthiarsih (Apollo: Journal of Tourism and Business, 2024)
People are becoming more aware of environmental difficulties in this time of globalization. Waste is one such problem, as waste is a major source of pollution in the air, soil and water. It is hoped that all individuals and businesses in Indonesia, including consumers, will increase awareness and concern for the environment as an effort to preserve and restore the earth's ecosystem. Emina products are one example of a company that prioritizes sustainability in its systems and products at PT Technology and Innovation. Emina is considered a product that contributes to a positive reputation and values social responsibility. Green marketing includes all efforts and endeavors directed at promoting, packaging, distributing, consuming, and recalling products through environmental awareness or response. Corporate social responsibility is a condition in which businesses must continue to pay attention to the environment in an effort to reduce environmental problems that have occurred or are occurring. To achieve sustainable growth and performance, corporate social responsibility is an initiative that is integrated into the investment strategy and is considered a corporate social obligation. Brand image, alongside environmental concerns and corporate social responsibility will emerge as an important consideration for companies in the coming years. Consequently, brand image is consumers' and customers' perception of a brand, which in turn inspires trust in the brand. This research highlights the importance of green marketing and environmental accountability in general by building a good perception of the organization's brand within the local community. The purpose of this study is to determine the correlation between brand image (Z) and the impact of corporate social responsibility (Y) and green marketing (X). Uncertainty surrounds most Emina product users who make up the population of this study. In the absence of population information, the sample size for a given study will be calculated based on criteria for an unknown population, resulting in a total of 100 respondents. This research will use a purposive sampling method, which involves selecting a sample from the population under study based on certain criteria. Regression analysis and path analysis will be used to analyze the data. Hypothesis testing, validity and reliability tests, normality and multicollinearity tests, path analysis model fit tests, and SPSS and AMOS Softwer analysis tools will be used for data analysis. According to the findings of this study, green marketing influences consumer perceptions of Emina products favorably, thereby contributing to improved environmental stewardship. Emina is perceived as an ethical and socially responsible entity, which positively impacts its reputation